An Annotated Arthur Schnitzler Bibliography Editions and Criticism in German, French, and English, 1879-1965 - Allen, Richard H. (UNC Studies in the Germanic Languages and Literatures, 1967)
Originally published in 1967, Richard H. Allen's volume with a foreword by Robert O. Weiss was the first comprehensive bibliography of Arthur Schnitzler's writings, including his literary works (with translation and criticism), philosophical reflections, essays, correspondence, and medical writings, together with general criticism and dissertations on the author. Indices of titles, personal names, and periodicals make the material readily accessible.